Republic of Moldova : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2010)
The composition of short-term and medium-term adjustment measures will facilitate sufficient short-term adjustment flexibility, and be consistent with medium-term fiscal sustainability. Improving debt resolution instruments will help the banks to regain confidence in lending. Meanwhile, there is a need to consider improvements in its liquidity framework. The main factors that shaped the economic growth model in Moldova in the last decade and the risks of the current growth model are outlined. Public policies can promote growth by identifying and addressing the most binding constraints to development.